Increasing Students Activity And Learning Outcomes In Fiqih Subjects Through Drill And Practice Methode At The Islamic Boarding School, Assalam Subang - Agus Budiman; Nurul Azizah; Muhammad Zakiyuddin (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
The research aim of this research is to know the implementation drill and practice method in learning fiqh material is hoped can to increase student activity and learning outcomes. Because it was found that the learning pattern still used conventional learning methods and there was no pressure on aspects of practice or training, it was found that 53% or 16 out of 30 students had not a minimum passing grade. This study used the Classroom Action Research method with the Kurt Lewin model with two cycles stages each cycle consists of planning, implementation, observation, and reflection. The results of this study are that implementation drill and practice methods can increase student activity in the first cycle with good results reaching 73% and in the second cycle with good results reaching 91%. The learning outcomes of students who have achieved a minimum passing grade in the first cycle with a result of % 60 and in the second cycle with a result of 100%.